1985
DOI: 10.1128/mcb.5.9.2221
|View full text |Cite
|
Sign up to set email alerts
|

Lens-specific promoter activity of a mouse gamma-crystallin gene.

Abstract: Crystallins are the major water-soluble proteins in vertebrate eye lenses. These lens-specific proteins are encoded by several gene families, and their expression is differentially regulated during lens cell differentiation.Here we show that a cloned mouse y-crystallin promoter is active in lens explants derived from 14-day-old chicken embryos but inactive in a variety of cells of nonlens origin. We also show that sequences required for proper utilization of this promoter are contained between nucleotide posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
38
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 59 publications
5
38
0
Order By: Relevance
“…In fact, wellcharacterized GC box-dependent genes have been either viral or housekeeping cellular genes (e.g., the simian virus 40, herpes simplex virus tk, and dehydrofolate reductase genes), and this is the first example of the involvement of a GC box in the expression of a tissue-specific gene. Among the crystallin genes which have been cloned and whose expression has been characterized (2,4,9,14,19), only the b-crystallin genes have GC boxes in their promoters. It is possible that interactions of a tissue-specific factor(s) with the B-crystallin promoter give rise to a potential for lensspecific b-crystallin expression, and binding of an Spl-like factor to the GC box may activate this expression.…”
mentioning
confidence: 99%
“…In fact, wellcharacterized GC box-dependent genes have been either viral or housekeeping cellular genes (e.g., the simian virus 40, herpes simplex virus tk, and dehydrofolate reductase genes), and this is the first example of the involvement of a GC box in the expression of a tissue-specific gene. Among the crystallin genes which have been cloned and whose expression has been characterized (2,4,9,14,19), only the b-crystallin genes have GC boxes in their promoters. It is possible that interactions of a tissue-specific factor(s) with the B-crystallin promoter give rise to a potential for lensspecific b-crystallin expression, and binding of an Spl-like factor to the GC box may activate this expression.…”
mentioning
confidence: 99%
“…Among other crystallins, a^-crystallin of mouse and chicken and 7-crystallin of mouse have been studied for expression of the cloned gene in cultured cells Okazaki et al 1985;Lok et al 1985) and in transgenic mice (Overbeek et al 1985;Goring et al 1987). In all of these cases, the 5'-flanking sequence of the genes directed lens-specific expression of linked genes, and it was found that the sequences upstream of -100 were essential for the lens specificity.…”
mentioning
confidence: 99%
“…In the otA-crystallin gene, the 5' flanldng sequence of the mouse (8) and hamster (10) is highly conserved; however, much of this similarity is lost in the chicken (21). In the mouse, rat, and human y-crystallin gene family there are several sequences upstream from the TATA box that are highly conserved (19,(22)(23)(24)(25). Except for the 81-crystallin gene (26,27), no other crystallin gene contains the 5'CCAAT3' sequence in their 5' flanking region (5,8,10,19,(22)(23)(24)(25)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…It is particularly interesting that crystallin promoters can function in lens cells ofheterologous species, even when the species from which the lens cells were derived do not contain the crystallin gene being tested. For example, the chicken 51-crystallin promoter can function in mouse lens cells (17,18), which do not contain endogenous 8-crystallin genes, and the mouse -y2-crystallin promoter can function in embryonic chicken y2 lens cells (19), which do not contain endogenous -y-crystallin genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation